Hybrid Aesthetic Values in Balinese Karawitan: The Role of Poetic Figurative Language in Bridging Tradition, Modernity, and Character Education - Ni Ketut Dewi Yulianti; Made Mantle Hood; I Komang Sudirga; I Gst. Ayu P. Jesika Sita Devi N (Universitas Udayana, 2026)
Balinese karawitan, a traditional musical form rooted in cultural expression, continues to evolve while sustaining its aesthetic foundations. This study examines hybrid aesthetic values in Balinese karawitan by analyzing how poetic figurative language functions as a mediating device between tradition, modern musical expression, and character education. Using a descriptive qualitative approach, the research analyzes four compositions: Ngoner Ngakung (Love That Blossoms), Sekar Layu (Withering Flower), Janger Ngapat (A Celebration of Fertility and Gratitude), and Kenangan Manis (Sweet Memories), to demonstrate how metaphors and other figurative forms deepen vocal aesthetics and intensify emotional resonance. The findings show that poetic imagery rearticulates traditional symbolic vocabularies within contemporary vocal styles, transforming musical narratives into ethical reflections on love, impermanence, gratitude, and nostalgia. Through this process, figurative language translates cultural meaning into values such as empathy, resilience, respect, and compassion. The study highlights poetic figurative language as an aesthetic bridge that sustains cultural identity while enabling moral formation within modern creative practice.